Waspada Diabetes Melitus melalui Skrining Kadar HbA1c pada Populasi Usia Lanjut di Panti Werdha Hana - Santoso, Alexander Halim; Lumintang, Valentino Gilbert; Alvianto, Fidelia (BADAN PENERBIT STIEPARI PRESS, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease that often goes undiagnosed in the elderly population, despite its long-term impact on quality of life and the risk of chronic complications. Through this community service activity, HbA1c screening was conducted for 76 elderly residents at Panti Werdha Hana as an early detection effort for diabetes mellitus, accompanied by education on healthy eating patterns and the importance of physical activity in diabetes prevention. The results showed an average HbA1c level of 5.99%, with 21.54% of participants identified in the diabetes category and 38.46% in the prediabetes category. These findings emphasize the importance of routine screening in the elderly, as the majority of participants had HbA1c levels exceeding normal thresholds. This program successfully identified elderly individuals with abnormal blood glucose levels and increased their awareness of the importance of early detection as an integral part of diabetes management. Keywords: Early Detection, Elderly, Diabetes Mellitus, HbA1c